Penatalaksanaan Fisioterapi pada Kasus De Quervain Syndrome Dextra dengan Modalitas Ultrasound dan Terapi Latihan di RSUD Cililin Kab. Bandung Barat - Eli Amelia; Ika Rahman; Abdul Qudus (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
De Quervain Syndrome is a musculoskeletal condition affecting the wrist, characterizted by pain on the radial side caused by inflammation of the abductor pollicis longus and extensor pollicis brevis tendons, which leads to limited range of motion and reduced functional ability. This study aimed to evaluate the effectiveness of combining ultrasound therapy with active exercise in reducing pain, improving range of motion, and enhancing functional ability in a patient with right-sided De Quervain Syndrome. A quantitative descriptive case study design was applied to one patient at RSUD Cililin, West Java Bandung. Outcome measures included the Visual Analog Scale (VAS), goniometer assessment, and Wrist and Hand Disability Index (WHDI), conducted over six treatment sessions. The findings indicated clinical improvement, including reduced resting pain (2 to 0), tenderness (5 to 2), and movement pain (5 to 2). Range of motion also increased in thumb flexion (35°-48°), extension (76°-88°), and abduction (18°-27°). Furthermore, the WHDI score decreased from 58% to 24%, reflecting a shift from severe to moderate disability. These result suggest that the combination of ultrasound and active exercise is effective in improving patient outcomes in De Quervain Syndrome.